Active and reactive power control for a hybrid system with photovoltaic panel, wind turbine, fuel cells, electrolyzer and super capacitor in off-grid mode - Palizban, O.; Rezaei, M.A.; Mekhilef, Saad (2011)
This paper proposes a hybrid system which consists of a photovoltaic panel, wind turbine, proton exchange membrane fuel cell (PEMFC), electrolyzer, super capacitor, power convertor and a three-phase variation load. The load supplied is based on the photovoltaic panel and wind turbine, while the fuel cells are back-up for compensating possible power load shortage. The surplus of power produced will be stored in a hydrogen tank by an electrolyzer system when the PV panel and wind turbine produce more power than required. The capacitor banks are used in parallel with other sources in order to reduce DC bus variation. Matlab software is chosen for the hybrid system simulation.